Fulfilled Emotional Outcome Expectancies Enable Successful Adoption and Maintenance of Physical Activity - Klusmann, Verena; Musculus, Lisa; Sproesser, Gudrun; Renner, Britta (Frontiers in Psychology, 2016)
Although outcome expectancies are regarded as key determinants of health behavior change, studies on the role of their degree of fulfillment in long-term activity changes are lacking. This study investigated the impact of (un-)fulfilled outcome expectancies (OE) on (un-)successful attempts to increase physical activity, assuming that disengagement is the logical consequence of perceived futility. Participants (n = 138) of a longitudinal cohort study with three measurement waves were assigned to eight different groups according to a staging algorithm of their self-reported, one-year-long physical activity behavior track. Stages were validated by objective changes in objective fitness, e.g. Physical Working Capacity (PWC). Social cognitive variables, self-efficacy, proximal and distal OE and fulfillment of OE, were assessed via self-report. Discriminant analyses revealed that OE fulfillment was the predominant predictor for differentiating between successful and unsuccessful behavior change. Amongst OE, proximal OE concerning emotional rewards, in conjunction with action self-efficacy, further improved discriminatory power. OE adjustment warranting hedonic rewards appears to be a crucial mechanism as it facilitates long-term changes through interventions aimed at increasing physical activity rates. Theoretical models might benefit by including the concept of fulfilled expectations acting in terms of feedback loops between volitional and motivational processes.